Collect, Save, Adapt: Making and Unmaking Ex Situ Worlds - Laboissiere, Anna-Katharina (UNIV TECHNOLOGY, SYDNEY-UTS EPRESS, 2019)
‘Putting the right species back in the right place’: expressed in the words of Bruce Pavlik, the Head of Restoration Ecology at the Millennium Seed Bank at Kew Gardens in a fundraising clip for the Breathing Planet Campaign, the work of biodiversity repositories seems straightforward. A simple matter of renewing the colonial and capitalistic capture of nature by exhausting its diversity in collecting, and then of reinserting species, suspended in the form of genetic information, into the neat spaces their disappearance or almost-dispappearance has left in their original ecosystems, the redemptive value of biodiversity repositories seems unquestionable. ‘There is no technological reason why any species should go extinct’, the clip goes on. The cryopreservation of genetic material in seed banks and ‘frozen zoos’ is often and justifiably understood as genetic-fetishistic suspension, several times removed from animal lives in actual habitats; I propose however to read them as world-making devices in their own right too, more entangled and entangling than they might present themselves to be. Collecting and saving are two mandates that have effects both on the species whose genetic information is banked and on the natures that are made possible or impossible through the projects delineated by biodiversity repositories; but they have also been implicated in a third such mandate, the assisted adaptation of species to anthropogenic climate change (be it the plan for ‘chaperoned assisted relocation’ proposed by the Missouri Botanical Garden or the ‘cultivation of marginally hardy taxa’ proposed at the Arnold Arboretum). How are biodiversity repositories an active intervention into the shaping of natures both inside and outside, and what are the consequences of what happens within the apparatus of these repositories for wider understandings of landscapes and species under threat? How linked is the suspension of metabolic processes and evolutionary potential and the understanding of Earth as manageable, perhaps even terraformable? What do they contribute to conservation biology’s biopolitical and cultural shaping of individuals, species, ecosystems suspended and remade through the different uses for which biodiversity repositories can be put to work?